2017
DOI: 10.1155/2017/9478958
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Naringenin-Oxime on Cisplatin-Induced Toxicity in Rats

Abstract: The aim of this study is to examine the protective effect of naringenin-oxime (NOX) on cisplatin-induced major organ toxicity and DNA damage in rats. Thirty-five male Wistar albino rats were equally split into five groups as follows: control (i.p., 0.1 ml of saline), Cis administration (i.p., 7 mg/kg b.w.), NOX treatment (i.p., 20 mg/kg b.w., daily for ten days), Cis + NOX20, and Cis + NOX40 combination (i.p., 20 and 40 mg/kg b.w., daily for ten days). Serum and peripheral blood mononuclear leukocytes (PBMC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 56 publications
9
46
0
Order By: Relevance
“…In addition, no biochemical toxicity was observed in treated rats, as shown in Table , thus providing evidence that Cℓ‐HIN is not hepato‐ or nephrotoxic. These results are in agreement with Koyuncu et al which showed that oxime treatment is non‐toxic to rodents . Collectively, these data suggest that a single dose of 300 mg/kg of Cℓ‐HIN is safe in rodents, which is in agreement with studies that reported similar LD 50 values for other classical oximes (pralidoxime and obidoxime)…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, no biochemical toxicity was observed in treated rats, as shown in Table , thus providing evidence that Cℓ‐HIN is not hepato‐ or nephrotoxic. These results are in agreement with Koyuncu et al which showed that oxime treatment is non‐toxic to rodents . Collectively, these data suggest that a single dose of 300 mg/kg of Cℓ‐HIN is safe in rodents, which is in agreement with studies that reported similar LD 50 values for other classical oximes (pralidoxime and obidoxime)…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with Koyuncu et al which showed that oxime treatment is non-toxic to rodents. 51 Collectively, these data suggest that a single dose of 300 mg/kg of Cℓ-HIN is safe in rodents, which is in agreement with studies that reported similar LD 50 values for other classical oximes (pralidoxime and obidoxime). 52 Isatin is an endogenous compound present in plants and human beings.…”
Section: Discussionsupporting
confidence: 89%
“…PmEO100CP and BCP pre-treated rats significantly restored protein carbonyl content in the liver similar to the role of natural product on protein carbonylation previously shown by Mohamed et al (2013). 8-OHdG is the most significant indicator of DNA damage (Koyuncu et al 2017). According to Cadet (2014), hydrogen from nucleic acids being eliminated by hydroxyl radicals or reacted with double bonds may lead to production of 8-OHdG.…”
Section: Discussionsupporting
confidence: 79%
“…Our results demonstrated that 8-OHdG is significantly increased in cisplatin-treated rats as compared to the control group. Previous studies showed that DNA damage was significantly inhibited by pre-treatment with natural compounds (Ince et al 2014;Koyuncu et al 2017). PmEO100CP and BCP likely used its antioxidant activity and decreased ROS-mediated 8-OHdG production.…”
Section: Discussionmentioning
confidence: 99%
“…The drug, cisplatin (CP), used in the treatment of cancer, has toxic effects on liver, kidney and genes. In a study conducted on rats, it was shown that when rats were first treated with naringenin-oxime (NOX) which is produced from naringenin and then CP was injected to rats, NOX showed an antioxidant effect and reduced the oxidative stress and DNA damage (21).…”
Section: Anti-oxidant Activitymentioning
confidence: 99%